PERCEPTION OF RURAL YOUTH TOWARDS FARMING AS AN OCCUPATION IN PUNJAB - ANJANA RAI *; KIRANJOT SID (The Journal of Research ANGRAU, 2022)
The purpose of the research was to study the perception of the 200 rural youth studying in class 10th/11th/12th aged 14-19 years in Punjab state towards farming as an occupation. Economic, socio-cultural, personal, physical and psychological factors were worked out to measure the perception of youth towards farming as an occupation. The findings of the study revealed that nearly three fourth of the respondents (71.5%) perceived that farming was not economically profitable occupation and they were dissatisfied with the income earned from farming. Nearly half of the sample (49%) agreed that other occupations can be undertaken along with farming as farming is seasonal and gives enough time to be involved in other subsidiary occupations. Most of the respondents (91%) agreed that farmers can earn throughout their life as there is no retirement age for farming. Youth (95.5%) also perceived that farming has as a low social status and it was also considered as physically laborious occupation by 97.5 percent of the respondents and most of the youth (98%) viewed that farming is associated with health risks due to exposure to heat, cold, dust and chemicals. However, majority (84%) of the youth believed that hard work in farming kept them healthy. More than three fourth of the sample youth (78.5%) dislike farming and were disinterested. Three fourth of the respondents (75%) were dissatisfied with income from farming as it was insufficient to fulfil their family expenditure.